The structural model of predicting family health based on communication patterns and self-efficacy with the mediating role of self-compassion in women - Janbozorgi, Fatemeh; Darbani, Seyed Ali; Parsakia, Kamdin (Psychology of Woman Journal, 2020)
The present study aimed to determine the structural model of predicting family health based on communication patterns and self-efficacy with the mediating role of self-compassion in women. In terms of the research method, the present research was of the predictive correlation type, and the goal was fundamental. The statistical population of the research included undergraduate and graduate students of Valiasr University Complex, Islamic Azad University, South Tehran Branch, who are members of the online student groups of the university in the 2019-2020 academic year. Based on this, 270 students were considered a sample using the available sampling method. To collect data, the family health questionnaire (Allen Jay et al., 1985), Christensen and Salavi's communication patterns questionnaire (1984), the self-efficacy questionnaire (Sherer et al., 1982), and the self-compassion questionnaire (Neff, 2003) were used. The research results showed that family health could be predicted based on self-efficacy and communication patterns. Also, self-compassion is mediating in predicting family health based on communication patterns and self-efficacy.